Comparisons of oblique lumbar interbody fusion and transforaminal lumbar interbody fusion for degenerative spondylolisthesis: a prospective cohort study with a 2-year follow-up - Wu, Jingye; Ao, Jintao; Xu, Zhongning; Li, Guanqing; Ge, Tenghui; Wang, Yongqing; Tao, Xiaohui; Tian, Wei; Sun, Yuqing (Frontiers in Surgery, 2023)
Objective: This study was aimed to compare the clinical outcomes between oblique (OLIF) and transforaminal lumbar interbody fusion (TLIF) for patients with degenerative spondylolisthesis during 2-year follow-up. Methods: Patients with symptomatic degenerative spondylolisthesis who underwent OLIF (OLIF group) or TLIF (TLIF group) were prospectively enrolled in the authors’ hospital and followed up for 2 years. The primary outcomes were treatment effects (changes of VAS and ODI from baseline) at 2 years after surgery, those were compared between two groups. Patient characteristics, radiographic parameters, fusion status, and complication rates were compared as well. Results: Totally 45 patients were eligible for OLIF group and 47 patients for TLIF group. The rates of follow-up were 89% and 87% at 2 years, respectively. The comparisons of primary outcomes demonstrated no different changes of VAS-leg (OLIF, 3.4 versus TLIF, 2.7), VAS-back (OLIF, 2.5 versus TLIF, 2.1) and ODI (OLIF, 26.8 versus TLIF, 30). The fusion rates were 86.1% in TLIF group and 92.5% in OLIF group at 2-years (P=0.365). OLIF group had less estimated blood loss (median, 200ml) than did TLIF group (median, 300ml) (P<0.001). Greater restoration of disc height obtained by OLIF (mean, 4.6mm) than did TLIF (mean, 1.3mm) at early postoperative period (P<0.001). The subsidence rate was lower in OLIF group than in TLIF group (17.5% versus 38.9%, P=0.037). The rates of total problematic complications were not different between two groups (OLIF, 14.6% versus TLIF, 26.2%, P=0.192). Conclusion: OLIF didn’t show better clinical outcomes than did TLIF for degenerative spondylolisthesis, except for less blood loss, greater disc height restoration and lower subsidence rate.